DERL3影响肺腺癌细胞A549增殖、侵袭转移的机制 (Zhongguo Fei Ai Za Zhi, 2020)
BACKGROUND AND OBJECTIVE: Derlin 3 (DERL3) is downregulated in colorectal cancer (CRC) samples. Its level is closely linked to lymphatic metastasis or distant metastasis rate in CRC patients. However, its biological behavior in lung adenocarcinoma were rarely reported. The aim of this study is to investigate the ectopic expression of DERL3 in lung adenocarcinoma tissues and its effect on the invasion and metastasis of lung adenocarcinoma A549 cell line to reveal the possible mechanism of invasion and metastasis of lung adenocarcinoma. METHODS: Lung adenocarcinoma microarray gene chip data included 3 cases of lymph node metastasis and 3 cases of lung adenocarcinoma tissue without lymph node metastasis. The GEDS and Kaplan-Meier plot queries the survival curve and expression level of DERL3. Western blot was used to detect the expression of DERL3 in lung adenocarcinoma cells. The efficiency of knockdown DERL3 gene was detected by Western blot assay. Transwell detected the number of cells passing through the basement membrane of the transwell. EDU assay detected cell proliferation ability. Western blot detected the expression of epithelial-mesenchymal transition related proteins E-cadherin and Vimentin. RESULTS: The microarray gene chip results showed that compared with lung adenocarcinoma tissues without lymph node metastasis, 1, 314 mRNAs in lung adenocarcinoma tissues with lymph node metastasis were up-regulated, 400 mRNAs were down (P < 0.05). The expression of DERL3 increased in lung adenocarcinoma (P < 0.05). The results of survival curve showed that the lung cancer patients with high expression of DERL3 with poor prognosis (P < 0.05). Western blot results indicated that plasmid transfection was successful. Knockdown of DERL3 suppressed the ability of proliferation, invasion and migration in A549 cells (P < 0.05). After knockdown of DERL3, the expression level of Vimentin was decreased, while E-cadherin expression increased (P < 0.05). CONCLUSION: Knockdown of DERL3 inhibited the proliferation, invasion and metastasis of A549 cells.